Tuberculous empyema in children - Nastiti N. Rahajoe; IGAN Partiwi; I. Boediman; Noenoeng Rahajoe; Bambang Supriyatno (Paediatrica Indonesiana, 1999)
We present a case of tuberculous empyema in a 14 month old girl. The diagnosis was primarily based on the history of the course of disease and a highly suspected contagious person. On physical examination, she was undernourished with enlargement of the lymph nodes prominently at the lateral of the neck. Aspiration of pleural fluid showed pus. Other findings were high blood sedimentation rate and a positive Mantoux test. The evidence of Mycobacterium tuberculosis from the pus culture confirmed the diagnosis. Before the diagnosis of pulmonary tuberculosis was established, cefuroxime was administered as the antibiotic of choice for eradicating any susceptible bacteria. Specific anti-tuberculosis therapy was then administered. In addition, water sealed drainage was performed in order to expand the lungs. However, this approach was insufficient due to abundant production of pus, therefore, surgical drainage was done with a good result. In order to avoid any further complications in the treatment of tuberculous empyema such as bronchopleural fistulas or drug resistancy, this child still requires a long-time follow up after discharged from hospital.